Where the heart stayed: a foreign student’s tale in Aceh - Abdul Razak, Mohd Abbas (Center for Community Development and Education (CCDE) Banda Aceh, Indonesia, 2025)
Aceh, located on the island of Sumatra, Indonesia, is a very special place for me, known for its vibrant people and natural beauty. The idea of pursuing my Islamic Studies at IAIN Ar-Raniry (now called UNIVERSITAS ISLAM NEGERI Ar-Raniry) was first suggested to me by my good friend, Ismail Abas—perhaps now a professor still teaching in Brunei Darussalam. At that time, in 1986, he was one of the pioneering foreign students in Aceh and was about to graduate from IAIN. Having spent several years in Aceh, my friend knew well how the application process worked. Earlier on, he had also recommended me for a position at the Islamic Propagation Centre in the South Pacific, a project planned by the Head of the Regional Islamic Da'wah Council of Southeast Asia and the Pacific (RISEAP). As a student leader, Ismail was well-connected with regional Islamic organizations. Standing at a crossroads between Aceh and the South Pacific, I reflected deeply on my path. After much contemplation, I chose Aceh. At that critical moment in my life, I believed that pursuing knowledge was more important than securing a job.